Effect of nanostructured zinc coating on high joining strength of polymer/galvanized high-strength steel composite via injection molding. (6th January 2023) - Chen, Weiyan; Kimura, Fuminobu; Kajihara, Yusuke
Abstract: This study proposed a hybrid joining technique for polymer and galvanized high-strength steel (GHSS) based on injection molding. Hot water treatment (HWT) was proposed to produce a nanoscale needle-like structure on the zinc coating surface to enhance the joining strength. We successfully obtained strong joints of GHSS and polybutylene terephthalate (PBT) via HWT with minimal damage to the zinc coating. The effects of HWT conditions on the tensile shear strength were evaluated and the optimized strength reached 23 MPa. The quantitative relationship between the nanostructured surface texture and the joining strength was analyzed. The number of structure peaks ( Np ) showed a strong positive correlation with the joining strength. The joining mechanism was investigated through TEM observation of the cross section and XPS analysis of the treated metal surface. Mechanical interlocking was the essential reason for the high joining strength. The results proved the feasibility of the proposed strategy and its potential for practical application.